Pengaruh Media Sosial Instagram, Citra Merek, dan Inovasi Produk terhadap Keputusan Pembelian : Studi pada Konsumen X Blok Y - Aditya Salsabila; Ravindra Safitra Hidayat; Maruji Pakpahan (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of Instagram social media, brand image, and product innovation on consumer purchasing decisions at Xlocated in Blok M Plaza, South Jakarta. The background of this study is based on the increasingly fierce competition in the culinary industry, especially in pastry products. This competition requires business actors to have the right marketing strategy, not only in terms of promotion, but also in maintaining brand quality and presenting product innovations that suit consumer needs. In the current digital era, social media has become one of the most powerful tools to influence consumer behavior. The research method uses a quantitative approach with a survey technique by distributing questionnaires to 100 respondents who are Xconsumers. The research instrument was compiled using a Likert scale, then the collected data were analyzed using the multiple linear regression method with the help of the SPSS application. This analysis aims to see how much influence the independent variables, namely Instagram social media, brand image, and product innovation have on the dependent variable, namely purchasing decisions. The results of the study show that all three variables have a positive and significant effect on consumer purchasing decisions. This means that the better the marketing strategy through Instagram, the stronger the brand image built, and the higher the level of product innovation, the consumer purchasing decisions will increase. These findings highlight the importance of integrating digital marketing with product development to achieve competitive advantage. The findings of this study provide practical implications for businesses, particularly in the culinary industry, to focus more on digital marketing strategies and product innovation that can meet consumer preferences and strengthen brand positioning in the market.